Um direito para todos?: reflexões sobre a relação entre direito à cidade, judicialização da saúde e planejamento urbano no município de Curitiba - Persicotti, Fabiana Guancino (2022)
The increasing urbanization has presented great challenges, among which those related to sanitation, urban mobility, housing, education and access to health, which fall on rights that make up the core of the right to the city. The analysis of the right to health from the perspective of the right to the city is relevant in the Brazilian context because the Federal Constitution of 1988 raised health to a category of fundamental social right and a duty of the State, although there are still many people deprived of its access, which characterizes the existence of different urbanities. The deficiencies related to the provision of the right to health are still far from being overcome by the State and, therefore, have been directed to the Judiciary. In this context, the present study seeks to understand the distribution of access to the Judiciary in the city of Curitiba in search of the right to health together with data related to the health of the population, analyzing them together from the perspective of the right to the city. As a general objective, we seek to point out which parameters could be used só that the diagnosis of the distribution of access to the Judiciary in search of the right to health can contribute to the construction of public policies for a more integrated city and, therefore, in line with the right to the city. As a general objective, we seek to point out which parameters could be used só that the diagnosis of the distribution of access to the Judiciary in search of the right to health can contribute to the construction of public policies for a more integrated city and, therefore, in line with the right to the city. The specific objectives consist of: discussing, based on an integrative bibliographic review, the right to the city and its relationship with space as a determining factor for access to citizenship, as well as the interconnections with public policies and urban planning; to compare data related to the health of the population of the city of Curitiba with the information regarding the lawsuits that deal with the right to health, filed in the Municipality of Curitiba between the years 2017 and 2020, before the Federal Court and State Court based on information anonymized obtained respectively from the Attorney General’s Office and the Attorney General’s Office of the State of Paraná; to point out how data from the judicialization of the right to health can help decisionmaking related to public health policies in the city of Curitiba. A total of 1,170 cases were analyzed, of which 830 are pending in the Federal Court and 340 in the State Court. The main results point out: the existence of a greater judicialization in areas of the city that are more integrated and in greater harmony with the right to the city; the important role of public institutions of legal assistance for the most vulnerable people and the indication of parameters obtained from the diagnosis of actions that can help actions and decisions related to urban planning and municipal public health policies.